2009
DOI: 10.1145/1462166.1462169
|View full text |Cite
|
Sign up to set email alerts
|

The computational power and complexity of constraint handling rules

Abstract: Constraint Handling Rules (CHR) is a high-level rule-based programming language which is increasingly used for general-purpose programming. We introduce the CHR machine, a model of computation based on the operational semantics of CHR. Its computational power and time complexity properties are compared to those of the well-understood Turing machine and Random Access Memory machine. This allows us to prove the interesting result that every algorithm can be implemented in CHR with the best known time and space c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 32 publications
0
52
0
Order By: Relevance
“…However, these results are based on the theory of language embedding, developed in the field of concurrency theory to compare Turing complete languages, hence they [117], where the authors show that it is possible to implement any algorithm in CHR in an efficient way, i.e. with the best known time and space complexity.…”
Section: Summary and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these results are based on the theory of language embedding, developed in the field of concurrency theory to compare Turing complete languages, hence they [117], where the authors show that it is possible to implement any algorithm in CHR in an efficient way, i.e. with the best known time and space complexity.…”
Section: Summary and Related Workmentioning
confidence: 99%
“…Even though in [117] it is shown that any algorithm can be implemented in CHR preserving time and space complexity, yet in [75] it is claimed that "priorities do improve the expressivity of CHR".…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation
“…The classical optimal unionfind algorithm [TvL84] can be implemented in CHR with best-known quasilinear time complexity [SF06,SF05]. This result is not accidental, since the paper [SSD05] shows that every (RAM machine) algorithm with at least linear time complexity (an algorithm that at least reads all of its input), can be implemented in CHR with best known time and space complexity. Such a result is not known to hold in other pure declarative programming languages.…”
Section: Constraint Handling Rules (Chr)mentioning
confidence: 99%
“…This paper presents a novel method by directly adding different weights for the information gain equation of every candidate attribution, and this way not only makes the selection of the optimal attribute more reasonable, but also has a small effect on the running speed. Secondly, as we all know, in two equivalent formulas (e.g., the logarithmic expression and the four arithmetic operation), the computation speed of the logarithmic expression is slower than that of the four arithmetic operations that only include add, subtract, multiply and divide [27]. Hence, this paper changes the logarithmic expression of the information gain of ID3 into the form of the four arithmetic operations by introducing the Taylor formula for developing in real time.…”
Section: Introductionmentioning
confidence: 99%